The first order L-G phase transition in liquid Ag and Ag-Cu alloys is driven by deviatoric strain. (15th March 2021) - An, Qi; Johnson, William L.; Samwer, Konrad; Corona, Sydney L.; Goddard, William A.
Abstract: An undercooled liquid-phase (L-phase) can undergo a first order configurational phase transition to either a crystal phase (X-phase) or a metastable, configurationally heterogeneous, rigid glassy phase (G-phase). To investigate the underlying mechanism of the L-G transition, we employ molecular dynamics simulations to study G-phase formation in a binary Cu-Ag system. We find that G-phase formation is driven by the reduction of local distortion energy arising from deviatoric strains in the liquid phase and demonstrate its local distribution. Reduction of distortion energy contributes over 80% of the latent heat of the L-G transition, suggesting that condensation of spatially varying random elastic fields in the liquid is primarily responsible for the first order L-G transition. By applying this analysis to crystallization and G-phase formation in elementary Ag, we show that deviatoric strain energy is the dominant driving force for the L-G and L-X transition also in the case of the pure metal. Graphical abstract: Image, graphical abstract